Chemopreventive activity of systemically administered curcumin on oral cancer in the 4-nitroquinoline 1-oxide model - Gonçalves, Vinícius de Paiva [UNESP]; Ortega, Adriana Alicia C. [UNESP]; Guimarães, Morgana R. [UNESP]; Curylofo,Fabiana Almeida [UNESP]; Rossa Júnior, Carlos [UNESP]; Ribeiro, Daniel Araki; Spolidorio, Luis C. (Wiley, 2015)
Curcumin has therapeutic potential in preventing several types of cancer, including colon, liver, prostate, and breast. The goal of this study was to evaluate the chemopreventive activity of systemically administered curcumin on oral carcinogenesis induced by 4-nitroquinolone-1-oxide (4-NQO). A total of 50 male albino rats, Rattus norvegicus, (Holtzman), were divided into five groups (n=10 per group). Four of these groups were exposed to 50 ppm 4-NQO in their drinking water ad libitum for 8 or 12 weeks, two groups were treated with curcumin by oral gavage at 30 or 100 mg/kg per day, and one group was treated with corn oil (vehicle) only. The negative control group was euthanized at baseline. Tongues of all animals were removed after euthanasia and used in the subsequent analysis because the tongue is the primary site of carcinogenesis in this model. Descriptive histological analysis and immunohistochemistry for PCNA, Bcl-2, SOCS1 e-3, and STAT3 were performed to assess the oncogenic process. The gene expression of Vimentin, E-cadherin, N-cadherin, or TWIST1 was assessed using RT-qPCR as a representative of epithelial-mesenchymal transition (EMT) events. The administration of curcumin at 100 mg/kg during the 12 weeks markedly decreased the expression of PCNA, Bcl-2, SOCS1 e -3, and STAT3. Curcumin also minimized the cellular atypia under microscopic analysis and diminished the expression of the genes associated with EMT. These findings demonstrate that the systemic administration of curcumin has chemopreventive activity during oral carcinogenesis induced by 4-NQO.